Superior semicircular canal dehiscence and subsequent closure induces reversible impaired decision-making - Mowery, Todd M.; Wackym, P. Ashley; Nacipucha, Jacqueline; Dangcil, Evelynne; Stadler, Ryan D.; Tucker, Aaron; Carayannopoulos, Nicolas L.; Beshy, Mina A.; Hong, Sean S.; Yao, Justin D. (Frontiers in Neurology, 2023)
Background Vestibular loss and dysfunction has been associated with cognitive deficits, decreased spatial navigation, spatial memory, visuospatial ability, attention, executive function, and processing speed among others. Superior semicircular canal dehiscence (SSCD) is a vestibular-cochlear disorder in humans in which a pathological third mobile window of the otic capsule creates changes to the flow of sound pressure energy through the perilymph/endolymph. The primary symptoms include sound-induced dizziness/vertigo, inner ear conductive hearing loss, autophony, headaches, and visual problems; however, individuals also experience measurable deficits in basic decision-making, short-term memory, concentration, spatial cognition, and depression. These suggest central mechanisms of impairment are associated with vestibular disorders; therefore, we directly tested this hypothesis using both an auditory and visual decision-making task of varying difficulty levels in our model of SSCD. Methods Adult Mongolian gerbils (n = 33) were trained on one of four versions of a Go-NoGo stimulus presentation rate discrimination task that included standard (“easy”) or more difficult (“hard”) auditory and visual stimuli. After 10 days of training, preoperative ABR and c+VEMP testing was followed by a surgical fenestration of the left superior semicircular canal. Animals with persistent circling or head tilt were excluded to minimize effects from acute vestibular injury. Testing recommenced at postoperative day 5 and continued through postoperative day 15 at which point final ABR and c+VEMP testing was carried out. Results Behavioral data (d-primes) were compared between preoperative performance (training day 8–10) and postoperative days 6–8 and 13–15. Behavioral performance was measured during the peak of SSCD induced ABR and c + VEMP impairment and the return towards baseline as the dehiscence began to resurface by osteoneogenesis. There were significant differences in behavioral performance (d-prime) and its behavioral components (Hits, Misses, False Alarms, and Correct Rejections). These changes were highly correlated with persistent deficits in c + VEMPs at the end of training (postoperative day 15). The controls demonstrated additional learning post procedure that was absent in the SSCD group. Conclusion These results suggest that aberrant asymmetric vestibular output results in decision-making impairments in these discrimination tasks and could be associated with the other cognitive impairments resulting from vestibular dysfunction.